Reduced Lattice Constant in Al‐Doped LiMn2O4 Nanoparticles for Boosted Electrochemical Lithium Extraction - Tan, Guangcai; Wan, Shun; Chen, Jie‐Jie; Yu, Han‐Qing; Yu, Yan (Advanced materials (Weinheim), 2024)
Extracting lithium selectively and efficiently from brine sources is crucial for addressing energy and environmental challenges. The electrochemical system employing LiMn2O4 (LMO) electrodes has been recognized as an effective method for lithium recovery. However, the lithium selectivity and stability of LMO need further enhancement for its practical applications. Herein, the Al‐doped LMO with reduced lattice constant is successfully fabricated through a facile one‐step solid‐state sintering method, leading to enhanced lithium selectivity. The reduced lattice constant in Al‐doped LMO is proved through spectroscopic analyses and theoretic calculations. Compared to the original LMO, the Al‐doped LMO (LiAl0.05Mn1.95O4, LMO‐Al0.05) exhibits highercapacitance, lower resistance, and improved stability. Moreover, the LMO‐Al0.05 with reduced lattice constant can offer higher Li+ diffusion coefficient and lower intercalation energy revealed by cyclic voltammetry and multiscale simulations. When employed in hybrid capacitive deionization (CDI), the LMO‐Al0.05 obtains a Li+ intercalation capacity of 21.7 mg g−1 and low energy consumption of 2.6 Wh mol−1 Li+. Importantly, the LMO‐Al0.05 achieves a high Li+ extraction percentage (≈86%) with Li+/Na+ and Li+/Mg2+ selectivity of 1653.8 and 434.9, respectively, in synthetic brine. The results demonstrate that the Al‐doped LMO with reduced lattice constant could be a sustainable solution for electrochemical lithium extraction. Al‐doped LMO with reduced lattice constant could be a sustainable solution for electrochemical lithium extraction.